2006
DOI: 10.1016/j.transproceed.2006.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatitis C Virus on Renal Transplantation: Association With Poor Survival

Abstract: Data concerning the effect of hepatitis C virus (HCV) infection on the long-term outcome of patient and allograft survival are conflicting. We performed a retrospective study including all renal transplant recipients who underwent the procedure at our center between July 1983 and December 2004. We compared HCV-positive (n ϭ 155) versus HCV-negative (n ϭ 1044) recipients for the prevalence of anti-HCV, patient/donor characteristics, and graft/patient survival. The prevalence of HCV-positive patients was 12%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 19 publications
4
21
0
1
Order By: Relevance
“…Transplant procedures with HCV are associated with increased viral load and higher ALT levels. 6,7 Similar to the literature, we also found that survival of HCV-positive patients was significantly lower than for non-HCV recipients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Transplant procedures with HCV are associated with increased viral load and higher ALT levels. 6,7 Similar to the literature, we also found that survival of HCV-positive patients was significantly lower than for non-HCV recipients.…”
Section: Discussionsupporting
confidence: 89%
“…2 Hepatitis C virus in renal recipients has a significant long-term negative effect on patient and renal allograft prognosis, with death from infections significantly higher than among the non-HCV population. 6 Some authors have suggested that immunosuppression facilitates HCV replication and aggravates liver lesions. Transplant procedures with HCV are associated with increased viral load and higher ALT levels.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,19,25 One study reported a 5-to 22-fold increased risk of dying of infectious diseases. 17 In our experience, the presence of cirrhosis did not lead to an increased likelihood of death or graft loss secondary to infection compared with our HCV þ controls without cirrhosis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…25 About 40 to 50 of these transplantations are performed annually. 29 Gonwa et al 30 reported that patients who suffered from renal failure after liver transplantation had a 6-year survival rate of 27% if they remained on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of HCV positivity in cadaveric kidney donors vary from 1 to 12% worldwide (81). Transplant combination of HCV-positive donor and recipient showed lower graft and patient survival than in the positivenegative donor/recipient combination in most (47,94), but not all, studies (95). Although the risk of patient death is higher in the positive-positive combination, this is, however, lower than that of HCV patients remaining on dialysis (96).…”
Section: Natural History Of Hcv Infectionmentioning
confidence: 93%